Goals in motion: exploring goal setting among adults living with HIV who participated in an online community-based exercise intervention - Tai-Te Su; Soo Chan Carusone; Kiera McDuff; Francisco Ibáñez-Carrasco; Ada Tang; Ahmed M. Bayoumi; Ahmed M. Bayoumi; Ahmed M. Bayoumi; Ahmed M. Bayoumi; Mona Loutfy; Mona Loutfy; Mona Loutfy; et al. (Frontiers in Rehabilitation Sciences, 2025)
IntroductionAdults living with HIV may experience various health-related challenges in life. Exercise has been shown to provide numerous benefits. However, the specific goals that individuals aim to achieve through exercise are not well-documented. Our aim was to explore goal setting among adults living with HIV who participated in an online community-based exercise (CBE) intervention.MethodsWe conducted a multi-method, longitudinal study using data from a 12-month online CBE intervention study involving 6-month intervention and follow-up phases. Goal Attainment Scaling was used to quantify the number and types of goals set and achieved at each phase. We analyzed interview data with a subsample to identify experiences with and factors influencing goal setting.ResultsThirty-two participants initiated the intervention and were included in analyses. The majority were men (69%); median age of 53 years. Participants articulated a median of four goals before and after the intervention, most commonly related to increasing muscle, reducing weight, and improving strength. Approximately 50% of goals were achieved at the end of intervention and follow-up phases. Interview data (n = 10) indicated goal setting was influenced by personal health concerns, family, and perceived obligations to research. Most found goal setting personal and helpful, while some experienced challenges.ConclusionsAdults living with HIV prioritized physical-health-related goals during an online CBE intervention, with diverse experiences influencing their goal-setting process. Findings may inform the design and evaluation of online exercise programs for adults living with HIV. Clinical Trial Registrationidentifier (NCT05006391).